Role of Surgery in Vestibular Schwannoma following prior Stereotactic Radiosurgery - Zanib Javed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association)
Stereotactic radiosurgery (SRS) is widely used for treating vestibular schwannoma (VS), offering high tumour control rates, especially in small to medium-sized tumours. However, a subset of patients experiences SRS failure, requiring subsequent salvage microsurgery (MS). The primary reason for salvage surgery is continued tumour growth, but other causes include symptom progression and cystic enlargement. Salvage surgery is more challenging due to increased tumour adhesion to critical structures, resulting in higher complication rates, particularly for facial nerve preservation. Studies suggest subtotal resection may offer better outcomes than gross total resection in terms of facial nerve function, though treatment remains complex and outcomes vary. Keywords: Vestibular schwannoma, stereotactic radiosurgery, salvage surgery, facial nerve.